P53 The cost-effectiveness of HCV antiviral treatment for injecting drug user populations. (6th September 2011) - Martin, N K; Vickerman, P; Foster, G R; Miners, A; Hutchinson, S J; Goldberg, D J; Hickman, M
Abstract : Introduction: Injecting drug use is the main risk of HCV transmission in most developed countries. Hepatitis C virus antiviral treatment (peginterferon + ribavirin) is cost-effective for patients with no reinfection risk. Concerns about reinfection and non-compliance may discourage clinicians from treating injecting drug users (IDUs), despite the potential use of treatment as prevention in this population. Aim: Using a cost-utility analysis, we examined the cost-effectiveness of providing antiviral treatment for IDUs as compared to treating ex/non-IDUs or no treatment. Method: A dynamic model of hepatitis C transmission and disease progression among IDUs and ex-/non-IDUs was developed, incorporating: a fixed number of antiviral treatments allocated at the mild HCV stage over 10 years, no retreatment after initial treatment failure, and potential re-infection for cured IDUs. We performed a probabilistic cost-utility analysis estimating long-term costs and outcomes (measured in QALYs) and calculating the incremental cost-effectiveness ratio (ICER) to determine the cost-effectiveness of treating IDUs as compared to treating ex/non-IDUs or no treatment for three baseline IDU HCV prevalence scenarios (20%, 40%, and 60%). Results: Antiviral treatment of IDUs is the most cost-effective option in both the 20% and 40% baseline chronic prevalence settings, with ICERs as compared to no treatment (best supportive care) of £521 and £2539 per QALY saved, respectively. Treatment of ex/non-IDUs is dominated in these scenarios. At 60% baseline prevalence, treatment of ex/non-IDUs or IDUs is roughly equally cost-effective; treating ex/non-IDUs is more likely to be the most cost-effective option (with an ICER as compared to no treatment of £6803), and treating IDUs is dominated due to the high re-infection at this prevalence. A sensitivity analysis indicates that these rankings hold even when IDU SVR rates as compared to ex/non-IDUs are halved. Conclusion: Despite the possibility of re-infection, the model projections suggest that providing antiviral treatment to IDUs is the most cost-effective policy option in chronic prevalence scenarios <60%. Further research on how HCV treatment for injectors can be scaled up, and its impact on prevalence is warranted.